Public company CSR management based on local wisdom towards sustainable development - Suwandi Suwandi; Jaka Waskito; Dien Noviany Rahmatika (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
One form of the company's contribution to the maintenance and preservation of the surrounding community's finances is through the implementation of CSR based on local wisdom. Through this management, the company will be able to establish positive relationships with the community. This study uses a qualitative methodology, namely the methodology part of library research, and uses secondary data obtained through document analysis studies. The results of the study reveal that the management of CSR based on local wisdom by public companies leads to sustainable development and involves the implementation of the BRI Peduli Community Development Program. The program is to contribute to the improvement of environmental conditions, social conditions, and the economy. BRI Peduli's CSR program is implemented in three stages, namely socialization, implementation, and internalization. One of them is through the program carried out by PT BRI, the number of which continues to increase every year. The implementation and distribution of various programs and assistance from BRI demonstrates its commitment to sustainable development and the application of sustainable finance principles as a means of implementing Financial Services Authority Regulation 51/POJK.03/2017 concerning the Implementation of Sustainable Finance for Financial Services Institutions, Issuers, and Public Companies.